Analisis Efektivitas Penyaluran Pembiayaan Kredit Pemilikan Rumah (KPR) Syariah Pada Perumahan Bersubsidi Dengan Akad Murabahah (Studi Kasus Bank Sumut KCP Syariah Kota Baru Marelan) - Hanafi, Burhan; Anggraini, Tuti; Inayah, Nurul (Universitas Hamzanwadi, 2024)
This research aims to determine the effectiveness of distributing subsidized Sharia KPR financing to Bank Sumut KCP Syariah Kota Baru Marelan. For low-income people (MBR). The focus of this research is 1). What is the mechanism for distributing subsidized mortgages at Bank Sumut KCP Syariah in the city of Baru Marelan to low-income people, whether as permanent employees or traders who earn daily income. 2). What is the level of effectiveness of subsidized KPR distribution at Bank Sumut KCP Syariah in the city of Baru Marelan for low-income people (MBR). This method uses qualitative methods, namely interviews, observation and documentation. The results show that the distribution of subsidized KPR at Bank Sumut KCP Syariah Kota Baru Marelan with Murabahah contracts is effective for MBR. Through interviews with resource persons, it was found that the selection and disbursement process of funds was carried out well. This bank has clear procedures for accepting subsidized KPR. Apart from that, it can also be seen that in the last 5 years the demand for subsidized Sharia KPR has increased, this can be seen from the data obtained from sources. However, in this mortgage, of course there are problems related to bad credit in the mortgage, but the bank already has several ways to resolve this problem. The level of effectiveness of this program is quite effective because KPR distribution is given right on target to low-income people (MBR) both as permanent employees and daily earners